Soda water oceans in the shadow of the volcano - Lucieer, VL (University of Tasmania, 2018)
IMAS researchers Dr Vanessa Lucieer, Erica Spain and Amy Nau this week completed a 20-day voyage to New Zealands Bay of Plenty on the National Institute of Water and Atmospheric Research (NIWA)s RV Tangaroa, under the watchful eye of the of the Whakaari/White Island volcano (Whakaari pron: far-car-ri).The aim of the voyage was to enhance capability to acoustically detect and characterise liquid and gaseous targets in the water column of coastal oceans around 200 metres in depth.